Professional Self - Self Awareness And Career Choice - Zuhra Mirzotilloevna Radjabova (Euro Asian Journal Publishing, 2024)
Self-awareness is the identification of a person with his "I", which is the unification of the past and the future. Realizing one's "I" is also avoiding the realization of self-perceptions, emotions, and thoughts that are not related to reality. The student realizes that he is growing up and that there are certain tasks in front of him, that he must fulfill these tasks.
Keywords: personality; adolescent; creative thinking